Reasons and determinants of distrust in the COVID 19 vaccine - Jandrić-Kočić Marijana (Medicinski Glasnik Specijalne Bolnice za Bolesti Štitaste Žlezde i Bolesti Metabolizma "Zlatibor", 2022)
Introduction: Distrust in the COVID 19 vaccine is a global public health problem. It is conditioned by doubt in the effectiveness of the vaccine, fear of unpredictable future effects of the vaccine and preference for natural immunity. Objective: The aim of the study was to evaluate the predictors of hesitation with vaccination against COVID-19 in the unvaccinated adult population, and to determine their conditionality by sociodemographic factors. Methods: The research, as an epidemiological cross-sectional study, was conducted at the Health Center Krupa in Uni from March 15, 2021. to 15.05.2022. The study sample consisted of 174 people, 78 women and 96 men with an average age of 54.8 ± 13.43 years. The research instrument was a socio-demographic questionnaire and a questionnaire for determining attitudes about vaccinations. Student statistical t-test and ANOVA test were used in statistical data analysis. Results: 83.33% of respondents believed in the ability of the vaccine to provide protection against clinically manifest disease, 61.49% from asymptomatic infection, and 59.77% from serious complications of the disease. 94.40% of respondents thought that vaccines would have side effects in the future, 99.33% that there were undetected side effects, 90.23% that it would result in side effects in children. 90.23% of respondents believed in greater safety of natural immunity, 88.51% in longer duration, and 57.48% in higher efficiency. Conclusion: Extremely high distrust in vaccine safety was the most important provision in respondents' decision not to be vaccinated against COVID 19. On the other hand, just over half of respondents believed that the vaccine protected against serious complications of the disease and considered natural immunity more effective than vaccination against COVID 19. Apart from the slightly higher efficiency of the vaccine in university-educated and employed respondents, sociodemographic factors did not have a statistically significant effect on the attitudes of respondents about the vaccine against COVID 19.